2018
DOI: 10.1007/978-3-319-77932-4_30
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Cardiovascular Comorbidities with Associations in Dermatologic and Rheumatic Disorders

Abstract: Cardiology, dermatology, and rheumatology form a fascinating triad. Many skin and joint disorders are associated with cardiovascular comorbidities because they share etiologic elements. Female predominance is often remarkable and likely related to autoimmune pathology. Although studies have shown that X-encoded genes may be involved in the differences in immunity between males and females, other studies have also shown that sex chromosomes are irrelevant and that estrogens and androgens are responsible for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…Only allergies and muscular and rheumatic disorders were more frequent in females, as in previous reports. [23][24][25] Furthermore, males had a trend for more alcohol dependence, as previously reported in other settings than elective neurosurgery. [26] Concerning the histological nature of the intracranial lesions, meningioma was the most frequent diagnosis and occurred with a striking sex disparity.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Only allergies and muscular and rheumatic disorders were more frequent in females, as in previous reports. [23][24][25] Furthermore, males had a trend for more alcohol dependence, as previously reported in other settings than elective neurosurgery. [26] Concerning the histological nature of the intracranial lesions, meningioma was the most frequent diagnosis and occurred with a striking sex disparity.…”
Section: Discussionsupporting
confidence: 75%
“…Only allergies and muscular and rheumatic disorders were more frequent in females, as in previous reports. [23–25] Furthermore, males had a trend for more alcohol dependence, as previously reported in other settings than elective neurosurgery. [26]…”
Section: Discussionmentioning
confidence: 55%
“…It has also been observed that inflammation in skin diseases seems to be an active source of several pro-inflammatory cytokines and chemokines that may predispose patients to CV comorbidities. (Kerkhof & Khamaganova, 2018) Inflammation is known to play a central role in CVD. In the inflammatory cascade, a macromolecular structure called the "inflammasome" stands out.…”
Section: Justificationmentioning
confidence: 99%